Can we do better? Bridging the research to practice gap in patient blood management–optimizing 'audit & feedback' and the challenges of undertaking a national cluster‐randomized controlled trial. (30th September 2018) - Stanworth, Simon J; Lorencatto, Fabiana; Gould, Natalie; Grant‐Casey, John; Deary, Alison; Hartley, Suzanne; McIntyre, Stephen; Moreau, Lauren; Morris, Thomas; Patel, Riya; Smith, Isabelle; Smith, James; et al.
Abstract : Audit and Feedback (A&F) is a frequently used quality improvement strategy, which aims to improve patient care and outcomes. The impact of A&F has been subjected to research scrutiny; systematic reviews document only modest and variable effects, despite the likely high costs of A&F programmes, such as those undertaken nationally. To understand and enhance A&F, a programme of research termed AFFINITIE 'Development & Evaluation ofA udit andF eedbackIN terventions toI ncrease evidence‐basedT ransfusion practice';http://www.ccf.nihr.ac.uk/ PGfAR/about/Pages/Abstract.aspx?ID=12588) has been completed. AFFINITIE adopted a multidisciplinary approach that applied behavioural theory and evidence to optimize the design and delivery of feedback on transfusion practice. These interventions were then tested by embedding them in the context of transfusion national audits in two national randomized cluster trials. The audit topics were preoperative surgery management and use of blood in patients with haematological malignancies. Emerging findings included the scope to improve the design of feedback reports by the inclusion of additional behaviour change techniques and increasing the specificity and relevance of feedback (i.e. clarity around who the feedback is targeted at, providing feedback only on behaviours relevant to audit standards, selecting fewer, more concrete, and relevant standards). Other findings recognized the importance of robust data collection based on agreed and clearly stated standards. Also, given wide variation in how hospitals received, shared and responded to feedback, a consequent need was identified to better support hospitals to plan their response to feedback, including disseminating the reports to all relevant stakeholders with agreement on selecting local goals and plans.